Transborder data flows and data privacy law - Kuner, Christopher (Oxford : Oxford University Press, 2013)
Written by a renowned expert on data protection law, this work examines the history, policies, and future of transborder data flow regulation, and is the only text to provide a detailed legal analysis of its global implications.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Transborder data flow -- Law and legislation; Data protection -- Law and legislation